A teacher-librarian collaborative model in designing literacy learning in the era of the Merdeka curriculum - Zaeni Achmad Syam, Rifqi; Karimah Nursya'bani, Kinkin; Nurwa Indah, Rosiana; Rohayati, Yeti (Indonesian Journal of Educational Development (IJED), 2025)
This study aims to design a collaborative model between teachers and librarians in literacy learning aligned with the principles of the Merdeka Curriculum at Mutiara Bunda Elementary School in Bandung. The urgency of this research stems from the ongoing gap between curriculum demands and the limited collaboration among key stakeholders in literacy instruction. A qualitative approach with a case study design was employed to explore in depth the collaborative practices within an elementary school that has implemented the Merdeka Curriculum since 2022. Participants comprising teachers, the librarian, the principal, and students were selected through purposive sampling based on their active involvement in literacy activities. Data were gathered through interviews, participatory observations, and document analysis, and analyzed using thematic techniques. The findings reveal that teacher–librarian collaboration occurs through joint planning, project-based literacy implementation, and regular evaluations. Librarians take on expanded roles as facilitators and co-educators. The resulting model repositions the school library as a learning commons, enhancing students’ engagement, reading interest, and critical thinking. Despite challenges such as limited coordination time and insufficient thematic materials, the collaboration demonstrates positive impacts. The study recommends collaborative training programs and institutional policies to support cross-professional integration. The model is adaptable for other schools aiming to strengthen literacy learning under the Merdeka Curriculum framework.